The Implementation of Information Technology to Employee Performance: A Study at the Baraka Subdistrict Office - Hamiddin, Muh. Irwan Nur; Syam, Jumiati; Syafruddin, Muhammad; Dahrul, Andi (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2024)
Tujuan penelitian ini adalah untuk mengetahui dan menganalisis pengaruh sistem informasi terhadap kinerja karyawan/pegawai. Penelitian ini menggunakan metode kuantitatif dengan sumber data yang digunakan adalah data primer melalui penyebaran kusioner di Kantor Kecamatan Baraka, Kabupaten Enrekang. Sampel dalam penelitian ini sebanyak 35 orang yang mewakili pegawai tetap dan pegawai honorerer di Kantor Kecamatan tersebut. Analisis data yang digunakan adalah analisis regresi linier berganda. Hasil penelitian ini menunjukkan bahwa sistem informasi dan penerapanny bepengaruh positif dan signifikan terhadap kinerja pegawai pada Kantor Kecamatan Baraka, Kabupaten Enrekang. The purpose of this study was to determine and analyze the effect of information systems on employee performance. This research uses quantitative methods with the data source used is primary data through distributing questionnaires at the Baraka District Office, Enrekang Regency. The sample in this study was 35 people who represented permanent employees and honorary employees at the District Office. The data analysis used is multiple linear regression analysis. The results of this study indicate that information systems and their application have a positive and significant effect on employee performance at the Baraka District Office, Enrekang Regency.